1998
DOI: 10.1007/s004280050180
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin stimulates epithelial cell proliferation in the oesophagus of rats

Abstract: Gastrin can induce mitotic stimulation in the oxyntic mucosa of the stomach, sometimes leading to abnormal growth. We examined whether gastrin was able to influence cell proliferation in the oesophageal epithelium. Rats were treated with gastrin, omeprazole or saline for 3 days, or were subjected to fundectomy or sham operation. Bromodeoxyuridine labelling (LI) and mitotic (MI) indices were counted in the proliferative zone of the squamous epithelium. Infusion of exogenous gastrin, treatment with omeprazole or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Therefore, in vitro experiments that try to reproduce this phenomenon seem to be promising. By infusing 2.5 nmol ⅐ kg -1 ⅐ h -1 , it was reported that a level of ϳ0.15 nmol/l gastrin is reached in the serum (14), which is in a range similar to the concentrations we used in culture experiments. Experiments in vitro showed that gastrin exerts a strong mitogenic effect on ductlike cells, obtained by culturing acinar cells, as described previously (8).…”
Section: Gastrin Stimulates ␤-Cell Neogenesissupporting
confidence: 74%
See 1 more Smart Citation
“…Therefore, in vitro experiments that try to reproduce this phenomenon seem to be promising. By infusing 2.5 nmol ⅐ kg -1 ⅐ h -1 , it was reported that a level of ϳ0.15 nmol/l gastrin is reached in the serum (14), which is in a range similar to the concentrations we used in culture experiments. Experiments in vitro showed that gastrin exerts a strong mitogenic effect on ductlike cells, obtained by culturing acinar cells, as described previously (8).…”
Section: Gastrin Stimulates ␤-Cell Neogenesissupporting
confidence: 74%
“…In our model of PDL (3), an internal control is present: the unligated part, which remains unaffected histologically and allows us to discriminate between effects of gastrin on normal exocrine tissue and on transdifferentiated cells. We evaluated the effect of intravenously administered gastrin (8,14) from day 7 postligation; this treatment lasted for 72 h. saline treatment. The treatment lasted for 72 h, and rats were fasted for 2 h before being killed on day 10 after duct ligation.…”
mentioning
confidence: 99%
“…Given the finding of potential roles of gastrin precursors in stimulating human cancer growth in vitro [25,43,44] and animal cancer models in vivo [26, 28, It is well known that the effect of amidated gastrin on stimulating gastrointestinal cancer cell growth was mediated by gastrin/CCK2 receptors [15,17,18], a gastringastrin/CCK2 receptor loop was found in some human cancers [15,16,20,24] and targeting of gastrin/CCK2 receptor by peptide or antibody exhibited a therapeutic potential in colonic, pancreatic and hepatocellular carcinoma cell lines in vitro [46]. In animals, gastrin has been found to stimulate normal esophageal epithelium proliferation [31,47,48] and promote carcinogenesis [32]. In Barett's esophagus, gastrin induces proliferation [33], metaplasia [33], and reduced apoptosis [21], which were mediated by upregulated gastrin/CCK2 receptors [21,33].…”
Section: Discussionmentioning
confidence: 99%
“…In animals, amidated gastrin was previously shown to stimulate the proliferation of esophageal epithelium in rats by either omeprazole (a potent gastric acid inhibitor) induced hypergastrinemia or infused gastrin-17 [30,31]. Karaki et al [32] reported that hypergastrinemia in rats enhances chemical carcinogen induced esophageal carcinoma.…”
Section: Introductionmentioning
confidence: 96%
“…Activation of some members of the G-protein linked 7-transmembrane receptor family, such as the bombesin or gastrin receptors, is known to enhance the proliferation of some cells (Chu et al, 1996;Van Nieuwenhove et al, 1998;Shulkes and Baldwin, 1997;Rozengurt, 1998). Therefore, we next sought to determine whether Mip-3␣ also modulated pancreatic cancer cell growth.…”
Section: Effects Of Mip-3␣ On Cell Growth and Invasionmentioning
confidence: 98%